Toestande in die Unie van Suid-Afrika op die vooraand van die Eerste Wêreldoorlog - Nel, H.F. (Scientia Militaria - South African Journal of Military Studies, 2012)
Although the act of violence precipitating the First World War came unexpectedly, it was evident even before the turn of the century that thunder clouds were gathering across Europe and consequent events pointed to eventual conflict. The article below deals with the situation in the Union of South Africa on the eve of the First World War.